The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/14606925.2021.1936748
|View full text |Cite
|
Sign up to set email alerts
|

Circular Fashion: The New Roles of Designers in Organizations Transitioning to a Circular Economy

Abstract: To tackle global sustainability challenges of the Fashion Industry and ensure longterm viability, companies have slowly started integrating circular approaches. This paper explores if and how fashion designers can aid the transition towards a circular economy. For this purpose, 15 interviews with ten fashion designers working in This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivatives License (http://creativecommons.org/licenses/by-nc-nd/ 4.0/),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The authors also witnessed a limited knowledge of designers in sustainable design strategies, processes, or tools and a lack of collaboration inside the company's departments, thus limiting designers' overall impact in tackling the current fashion system. The study has been later confirmed and widened by Cristina Dan & Østergaard (2021) who highlighted organizational, structural, operational, and attitudinal barriers in the context of the designer's role within organizations shifting towards CE, calling for a wider sustainability-related knowledge and systemic organizational changes. Finally, although academic research has expanded the knowledge on sustainable design and suggested different tools over the years, still this theoretical knowledge has not been fully translated into workable industry practices.…”
Section: The Textile Sector and The Evolution Of Design For Sustainabilitymentioning
confidence: 76%
See 2 more Smart Citations
“…The authors also witnessed a limited knowledge of designers in sustainable design strategies, processes, or tools and a lack of collaboration inside the company's departments, thus limiting designers' overall impact in tackling the current fashion system. The study has been later confirmed and widened by Cristina Dan & Østergaard (2021) who highlighted organizational, structural, operational, and attitudinal barriers in the context of the designer's role within organizations shifting towards CE, calling for a wider sustainability-related knowledge and systemic organizational changes. Finally, although academic research has expanded the knowledge on sustainable design and suggested different tools over the years, still this theoretical knowledge has not been fully translated into workable industry practices.…”
Section: The Textile Sector and The Evolution Of Design For Sustainabilitymentioning
confidence: 76%
“…This reveals a limited knowledge of designers in framing the sustainability discourse on a broader perspective that includes the social, environmental, and economic domain, so the sustainable design's deeper significance has still to be recognized (Stebbing and Tischner 2015). Also, the designer's role inside the company is limited according to Cristina Dan & Østergaard (2021) who reported organizational, structural, operational, and attitudinal barriers. This calls for three important actions needed to broaden designers' knowledge and impact and address a deeper change into the current fashion system: first of all, the need for a strong focus on sustainability in design education curricula (Vercalsteren et al, 2019); secondly, to increase designers' collaboration inside companies' departments and outside with external stakeholders (Karell & Niinimäki, 2020;Mestre & Cooper, 2017;Ghisellini et al, 2016;Lane et al, 2015); third, a systemic approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Designers must integrate materials and design-driven strategies across supply chains rather than limit them to today's system's waste stage. Therefore, a shift in the designer's mindset must be enabled who can maximize, through their action, the sustainable potential of new biobased materials all along the chain [3].…”
Section: Introductionmentioning
confidence: 99%
“…160,000 companies (of which 99.8% are micro and small companies), employing 1.5 million people and generating a turnover of EUR 162 billion [16,17]. (3) The authors' organization's knowledge and experience, based on academic study, teaching, networks, projects, and other research and practice carried out by team members in fashion design for sustainability. Section 4 reports results and discussion about the analysis of current industry practices that embeds sustainability and circularity through a systemic approach aiming to transform the industrial material flows by investing in design and knowledge.…”
Section: Introductionmentioning
confidence: 99%